2020
DOI: 10.1016/j.jcmg.2020.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography Using High-Frame-Rate Imaging in the Follow-Up of Heart Transplantation Recipients

Abstract: Background: After orthotopic heart transplantation (HTx), allografts undergo diffuse myocardial injury (DMI) that contributes to functional impairment, especially to increased passive myocardial stiffness, which is an important pathophysiological determinant of left ventricular (LV) diastolic dysfunction. Echocardiographic shear wave (SW) elastography is an emerging approach for measuring myocardial stiffness in vivo. Natural SWs occur after mechanical excitation of the myocardium, e.g. after mitral valve clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
2
29
0
1
Order By: Relevance
“…The propagation speed of shear waves after mitral valve closure (ie, end‐diastole) appeared to be related to the degree of diastolic dysfunction and showed a good correlation with E/E', as well defined standard echocardiographic parameter for predicting diastolic filling pressures 24 . We further showed that in heart transplant recipients, end‐diastolic shear wave propagation velocities have a good correlation with parameters of cardiac magnetic resonance used as marker of diffuse myocardial injury (Figure 4) and were the best noninvasive parameter to correlate with pulmonary wedge pressures measurements, as a reflection of an increase in left ventricular filling pressures 25 …”
Section: Assessment Of Fast Tissue Motionsupporting
confidence: 56%
See 4 more Smart Citations
“…The propagation speed of shear waves after mitral valve closure (ie, end‐diastole) appeared to be related to the degree of diastolic dysfunction and showed a good correlation with E/E', as well defined standard echocardiographic parameter for predicting diastolic filling pressures 24 . We further showed that in heart transplant recipients, end‐diastolic shear wave propagation velocities have a good correlation with parameters of cardiac magnetic resonance used as marker of diffuse myocardial injury (Figure 4) and were the best noninvasive parameter to correlate with pulmonary wedge pressures measurements, as a reflection of an increase in left ventricular filling pressures 25 …”
Section: Assessment Of Fast Tissue Motionsupporting
confidence: 56%
“…Due to technical challenges related to image depth, intercostal sector imaging and a continuously moving target, first implementations of cardiac SWI have occurred only recently and studies investigating the use of SWI to quantify myocardial stiffness were initially mainly performed in open‐chest animal models 21–23 . Improvements in ultrasonography techniques demonstrated lately also the feasibility of this method in in vivo closed‐chest animals and humans 13,16,24,25 …”
Section: Assessment Of Fast Tissue Motionmentioning
confidence: 99%
See 3 more Smart Citations